Chemical and Thermal Changes in Mg3Si2O5 (OH)4 Polymorph Minerals and Importance as an Industrial Material - Sasmaz, Ahmet; Kilic, Ayse Didem; Konakci, Nevin (Mdpi, 2024)
Serpentine (Mg3Si2O5(OH)4), like quartz, dolomite and magnesite minerals, is a versatile mineral group characterized by silica and magnesium silicate contents with multiple polymorphic phases. Among the phases composed of antigorite, lizardite, and chrysotile, lizardite and chrysotile are the most prevalent phases in the serpentinites studied here. The formation process of serpentinites, which arise from the hydrothermal alteration of peridotites, influences the ratio of light rare earth elements (LREE) to heavy rare earth elements (HREE). In serpentinites, the ratio of light rare earth elements (LREE)/heavy rare earth elements (HREE) provides insights into formation conditions, geochemical evolution, and magmatic processes. The depletion of REE compositions in serpentinites indicates high melting extraction for fore-arc/mantle wedge serpentinites. The studied serpentinites show a depletion in REE concentrations compared to chondrite values, with HREE exhibiting a lesser degree of depletion compared to LREE. The high Sigma LREE/Sigma HREE ratios of the samples are between 0.16 and 4 ppm. While Ce shows a strong negative anomaly (0.1-12), Eu shows a weak positive anomaly (0.1-0.3). This indicates that fluid interacts significantly with rock during serpentinization, and highly incompatible elements (HIEs) gradually become involved in the serpentinization process. While high REE concentrations indicate mantle wedge serpentinites, REE levels are lower in mid-ocean ridge serpentinites. The enrichment of LREE in the analyzed samples reflects melt/rock interaction with depleted mantle and is consistent with rock-water interaction during serpentinization. The gradual increase in highly incompatible elements (HIEs) suggests that they result from fluid integration into the system and a subduction process. The large differential thermal analysis (DTA) peak at 810-830 degrees C is an important sign of dehydration, transformation reactions and thermal decomposition, and is compatible with H2O phyllosilicates in the mineral structure losing water at this temperature. In SEM images, chrysotile, which has a fibrous structure, and lizardite, which has a flat appearance, transform into talc as a result of dehydration with increasing temperature. Therefore, the sudden temperature drop observed in DTA graphs is an indicator of crystal form transformation and CO2 loss. In this study, the mineralogical and structural properties and the formation of serpentinites were examined for the first time using thermo-gravimetric analysis methods. In addition, the mineralogical and physical properties of serpentinites can be recommended for industrial use as additives in polymers or in the adsorption of organic pollutants. As a result, the high refractory nature of examined serpentine suggests that it is well-suited for applications involving high temperatures. This includes industries such as metallurgy and steel production, glass manufacturing, ceramic production, and the chemical industry.
Keywords: geological materials; DTA; TG; hydrothermal alteration; ophiolite